Community Radio Supporting Maternal and Child Health and Preventing obstetric Fistula in an area impacted by climate change - Shahriar, Selim; al Mahmood, Abdullah; Biswas, Nitta; Huda, Sk Nazmul; Nalta, Radio; Satkhira, - (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To describe how a community radio station and its allied resources have supported maternal and child health promotion and prevention of fistula in hard to reach and climate change-affected areas in Bangladesh. Methods: The volunteers and operators of Radio Nalta were provided training on maternal health and fistula communication by a development partner. Information packs were made available through different institutions. Results: We produced and broadcast public service announcements on maternal health and fistula, integrated maternal health and fistula related messages radio plays and prioritized maternal health and fistula coverage in community radio news. We aired 11 talk shows on fistula, eight in observation to International day to end obstetric fistula. We reached 600,000 people with fistula information. Conclusions: Community radio can help in reaching out populations in hard to reach areas with information and education for promoting maternal health and prevention of fistula. Coastal areas are impacted by climate change and the community radio can effectively communicate with communities there.